Men and the Suffrage - Kristmundsdóttir, Sigríður Dúna (Veftímaritið Stjórnmál og stjórnsýsla, 2016)
Around the turn of the last century the suffrage was a crucial political issue in Europe and North America. Granting the disenfranchised groups, all women and a proportion of men, the suffrage would foreseeably have lasting effects on the structure of society and its gendered organization. Accordingly, the suffrage was hotly debated. Absent in this debate were the voices of disenfranchised men and this article asks why this was so. No research has been found on why these men did not fight for their suffrage while women ́s fight for their suffrage has been well researched. Within this context, the article examines the case of Iceland, in terms of issues such as the importance of urbanization, social change and culturally defined perceptions of men and women as social persons. It is argued that men did not have the same impetus as women to fight for their suffrage, and that if they had wanted to they were in certain respects disadvantaged compared to women. The gendered organization of society emerges as central in explaining why women fought for their suffrage and men did not, and why women’s suffrage received more attention than men’s general suffrage. As a case study, offering a microcosmic view of the subject in one social and cultural context, it allows for comparison with other like studies and with ongoing social processes.